Clinical-microbiological profile in burned patients Caumatology Unit Dr. Rubén Sánchez Reyes (Boletin Médico de Postgrado, 2024)
A cross-sectional descriptive study was carried out to determine the clinical-microbiological profile of 52 patients with burns admitted to the Dr. Rubén Sánchez Reyes Caumatology Unit of the Dr. Antonio María Pineda Central University Hospital during the period January-June 2022. The main causative agent of the burns was direct fire (48.08%); the anatomical areas involved were upper limbs (48.08%), face (38.46%) and lower limbs (36.54%). Half of the patients had a burn extension of 21-40% and deep partial thickness of second degree; 65.38% had moderate burns and in 32.69% the hospital stay was between 41-50 days. The germs isolated in the first culture were P. aeruginosa (17.31%) and A. baumannii, Enterobacter Cloacae Complex, E. coli and S. aureus (13.46% c/u). In the second culture, S. aureus (25%), E. coli (21.15%) and P. aeruginosa (9.62%) were reported. The antibiogram results for the main Gram-positive and negative germs in the first culture showed high sensitivity to various antibiotics, as well as resistance. In the second culture after treatment, the persistence of S. aureus highly sensitive to linezolid, rifampicin and trimethoprim/sulfa, E. coli with high sensitivity to imipenem, meropenem and P. aeruginosa with intermediate sensitivity to piperacillin, tazobactam and aztreonam is reported. From the microbiological control study of surfaces, microbial growth of the Enterobacterales group and the Staphylococcus genus was reported. Careful selection of antibiotics for optimal treatment of burn wound infections helps to reduce morbidity and mortality associated with microorganisms resistant to antibiotic therapy.